Evaluation of the photocatalytic activity of iron oxide nanoparticles functionalized with titanium dioxide. (February 2016) - Herrera, A; Reyes, A; Colina-Márquez, J
Abstract: Photocatalytic activity of iron oxide (IO) nanoparticles functionalized with TiO2 was evaluated through photodegradation of phenol under UV irradiation. For this, magnetic nanoparticles were synthesized by co-precipitation method obtaining aggregates with a size of 46nm. The IO nanoparticles were encapsulated in a polysiloxane matrix and then functionalized with TiO2 at 25°C (sample A: 0.1g TiO2 and B: 0.3g TiO2 ). Photodegradation experiments were carried out for six hours at pH 3.0 using concentrations of IO-TiO2 nanoparticles of 0.2, 0.5, and 1.0g/L. A maximum amount of 89% of phenol photodegradation was achieved by using 0.2g/L of the IO-TiO2 -B sample. In addition, it was evaluated the possibility to re-using the nanomaterial after magnetic separation. For this, 0.2g/L of B sample were submitted for five cycles of photodegradation. A stable photocatalytic activity was observed as well as the nanoparticles were regenerated by calcination among cycles, which suggests the versatility of these nanoparticles for the photodegradation of organic pollutants.